A Numerical and Experimental Investigation for Deposition of Conductive Ink on Multiple Substrate with Different Surface Energy and Ink Surface Tension - Hasnul Fauzi, Mohamad Hannan Asyraf; Muhammad Najmi Zainal,; Rd Khairilhijra Khirotdin,; Wan Muhamad Syakir Wan Zaini , (Research Progress in Mechanical and Manufacturing Engineering, 2024)
A simulation study of fluid dynamic model representing the deposition process of silver conductive ink on three different substrate was conducted to predict the topological characteristics of the printed ink track and validated through experimental works using syringe deposition system. The model that was researched in previous study only applied for general substrate and this study aimed to improve the model by including substrate surface energy and ink surface tension. Deposition parameters including deposition speed, pressure deposition height and nozzle tip size were set constant while the type of substrate and viscosity of ink were varied and investigated. It was observed that both simulation and experimental outcomes demonstrated the effectiveness of the dynamic model used with regards to change of the topological characteristics when deposition parameters were varied. A higher substrate surface energy resulting in increment of line width while a higher viscosity and ink surface tension result in narrower line width. The finding showed an improvement of 22.95% error differences with the improved model when compared to 37.6% error differences with the previous model.